Autonomic adaption to clinical simulation in psychology students: teaching applications (2018)
Simulation is used to facilitate new learning in a variety of situations. One application of simulation could be to help therapists gain therapeutic skills prior to seeing clients. This particular study was interested in measuring changes in stress response by looking at subjective and objective measures of distress (as measured by SUDS, HR, and HRV) over three sessions of simulated therapy. 16 second year psychology students participated in three sessions, and had their HR and HRV measured by Polar watches. Over the three sessions, there was a decrease in perceived distress, as measured by SUDS ratings. During and between sessions, there was inconclusive change in physiological parameters.